Implementation of the Independent Curriculum in Junior High School Social Studies Learning - Muhammad Aqil, Muhammad Aqil; Amrin, Amrin (Yayasan Insan Mulia Bima, 2024)
The aim of this research is to describe the planning, implementation and assessment of social studies learning for class VIII SMP Negeri 2 Bolo. This type of research is descriptive qualitative. Data and information were obtained through observation, interviews and documentation. Then the data was analyzed in three stages, namely; reduction, interpretation and drawing conclusions. The results of this research illustrate several things, namely; 1) learning planning is determined through learning outcomes, instructional objectives outlined in the ATP (learning objective flow) combined with integrated modules from the independent curriculum; 2) Implementation of learning using PBL, PjBL, and cooperative learning or group learning models and strategies; 3) social studies learning assessment consisting of formative and summative tests; 4) The obstacles faced by teachers are difficulties in creating teaching modules and preparing instruments for assessing Pancasila student profile projects